Digital humanities - Carter, Bryan (Bingley, U.K. : Emerald, 2013)
The field of Digital Humanities is becoming more exciting as the number of low-cost or free mobile and desktop applications flood the market allowing users to accomplish tasks that only a few years ago were either not possible or required complicated coding or high-end computing power. The range of these applications provides access to digital communications, advanced visualization, data storage and retrieval at unprecedented levels. Digital Humanists are incorporating these tools as part of our teaching, research, and creative expression. This research volume approaches the topic from a perspective that will be attractive to those just beginning, through the step by step guides to set up and use of a variety of tools with accompanying objectives, and to those who are more advanced, through more challenging applications and their use for teaching and research. Furthermore this text will be of interest to administrators or those sceptical about the Digital Humanities, as the essays will highlight studies and research by experts in the field while maintaining the particular perspective on literary studies and Digital Africana Studies. This volume includes an introduction to the Digital Humanities and chapters on The Social Web, Communications, Visualization and Collaboration.
Introduction to digital humanities / Bryan W. Carter -- The social web / Bryan W. Carter -- Communicating with the world / Bryan W. Carter -- Visualizing the world and engaging the field / Bryan W. Carter -- Archiving and sharing our research / Bryan W. Carter -- Conclusion / Bryan W. Carter.
Includes bibliographical references and index.
Print version record
Keywords: Education -- Computers & Technology; Education -- Higher; Education -- General; "Educational equipment & technology, computer-aided learning (CAL)".; Colleges of higher education; Humanities -- Electronic information resources; Humanities -- Computer network resources